Jean Bodin and biopolitics before the biopolitical era - Lindholm, Samuel, author.
1 online resource.
Keywords: "This book offers fresh perspectives on the history of biopolitics and the connection between this and the technology of sovereign power, which disregards or eliminates life. By analyzing Jean Bodin's political thought, which acts as a prime example of early modern biopolitics and proves that the two technologies can co-exist while maintaining their conceptual distinction, the author combines Foucauldian genealogy with political theory and intellectual history to argue that Michel Foucault is mistaken in presuming that biopolitics is an explicitly modern occurrence. The book examines Bodin's work on areas such as populationism; censors; climates, humors, and temperaments; and witch hunts. This pioneering book is the first English-language volume to focus on the biopolitical aspects of Bodin's work, with a Foucauldian reading of his political thought. It will appeal to students and scholars of political theory, sovereignty, and governance"--